THE EXPRESSIONS OF EXCLAMATION: A CROSS-CULTURAL ANALYSIS IN AUSTRALIAN ENGLISH AND BAHASA INDONESIA - Adrefiza Adrefiza (IJEE (Indonesian Journal of English Education), 2014)
This study investigated and compared exclamatory expressions performed by native speakers of Australian English and Bahasa Indonesia. Three different contexts and situations were selected as the prompts for the respondents to express their exclamations: (a) surprise; (b) enthusiasm; and (c) annoyance. Based on data from 36 respondents of both languages, the findings revealed that both Australian English and Bahasa Indonesia were likely to utilize different types of exclamatory words, phrases or expressions of surprise, enthusiastic and annoyance. Te expressions seemed to be systematic in their constructions and the selection of words or phrases remained personal and indicated the speakers‟ feeling, attitude, and emotion. In expressing surprise and enthusiasm, in particular, the selection of words or phrases by both language communities tended to use positive and socially acceptable exclamatory expressions. However, when they turned to express annoyance, most of the words, phrases, or expressions used were often taboo and socially unacceptable.